1103 Lupus clinical flares in patients with gut pathobiont blooms share a novel peripheral blood transcriptomic immune activation profile. (14th December 2022) - Silverman, Gregg J; Cornwell, Macintosh; Izmirly, Peter; Buyon, Jill; Azzouz, Doua F; Ruggles, Kelly
Abstract : Background: SLE is an inflammatory condition associated with hyperactivation of the immune system, with mounting evidence that imbalances in the gut microbiota communities are common. These imbalances can range from subtle patterns of dysbiosis to blooms in abundance of individual species that are concordant with clinical disease flares. Based on preliminary longitudinal surveys, almost half of Lupus nephritis (LN) flares were concurrent with transient expansions of a pathobiont, Ruminococcus (blautia) gnavus . As the transcriptomic patterns in the cells in our bloodstream can reflect disease activity, we sought to investigate gene expression patterns in groups of lupus patients, with comparisons to healthy controls (HC). Methods: From a well-characterized cohort, exploratory studies were performed on a selected group of 15 active female SLE patients, based in part on SLEDAI scores > 4. Patients were grouped as without a history of renal involvement (i.e., non-renal) (N=7) or with LN in flare with Urine Protein creatinine ratio >0.5. Based on 16S rRNA fecal microbiota analyses, LN were subsetted as without bloom of individual species (N=4), or with a bloom ( > 20-fold increased from HC, 3-9% abundance) of R. gnavus (N=4). In comparisons with 8 female HC, bulk RNA-seq was completed and after standard QC and filtering, 24, 319 genes passed a minimum threshold of 4 reads in >50% samples and were used in downstream analysis. Results: Unsupervised clustering based on gene expression demonstrated significant separation between SLE samples and HC (figure 1). While there was no clear distinction between non-renal and renal (i.e., LN) groups, there were striking differences in the group of active LN without detectable gut microbiome blooms vs. active LN with R. gnavus blooms (figure 2), with 173 upregulated and 13 downregulated genes based on differential expression analysis (padj < 0.05, log2fc > 1). Gene set enrichment analysis (GSEA) identified several significantly altered pathways in the LN flare with blooms compared to no blooms, in highlighting multiple platelet activation pathways in the LN with blooms. In contrast, the LN flares without blooms had significantly higher interferon alpha and interferon gamma signatures. Conclusion: Our findings document two major types of flares of LN, with one being mediated by higher PBMC IFN- type I and -gamma transcript levels, and a second without this signature that instead is dominated by several pathways for platelet activation that can be responsible for systemic thromboinflammation. This second distinct pathways of immune activation in PBMC of LN in flare was concurrent with gut blooms of R. gnavus, a pathobiont that induces increased gut permeability, systemic inflammation, bacterial translocation and autoantibody production, which has a well-established association with active Lupus Nephritis. These findings may indicate that in a major subset of patients, LN flares may arise from severe perturbations of intestinal communities associated with a leaky gut, Together, this highlights R. gnavus as a potential causative agent for Lupus flares, in which we hypothesize that gut leak of innate immune stimuli, such as TLR2 and TLR4, which activate platelets in immune hyperactivation pathways that underlie lupus autoimmune pathogenesis.